2007
DOI: 10.1111/j.1447-0756.2007.00504.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of laparoscopic ovarian drilling for polycystic ovary syndrome resistant to clomiphene citrate

Abstract: Patients with PCOS as diagnosed based on the Japanese diagnostic criteria include those with increased and normal androgen levels. LOD is considered an effective ovulation induction method for both types of patients with PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 13 publications
1
10
0
2
Order By: Relevance
“…Laparoscopic ovarian drilling (LOD) is accepted widely as secondline treatment of patients with polycystic ovary syndrome (PCOS) after failure of clomiphene citrate (CC) therapy (1)(2)(3). Currently the optimum amount of electrosurgical energy needed during LOD to achieve maximum reproductive outcome without risks is uncertain (4).…”
mentioning
confidence: 99%
“…Laparoscopic ovarian drilling (LOD) is accepted widely as secondline treatment of patients with polycystic ovary syndrome (PCOS) after failure of clomiphene citrate (CC) therapy (1)(2)(3). Currently the optimum amount of electrosurgical energy needed during LOD to achieve maximum reproductive outcome without risks is uncertain (4).…”
mentioning
confidence: 99%
“…We reported an 86% ovulation rate in group 2, which is almost similar to the 84.2% reported by Kato et al [23] and the 73.2% reported by Felemban et al [24]. Although LOD is appropriate for patients who have not ovulated using oral medications and are unwilling or unable to use gonadotropins, it is a costly procedure that must be performed by highly trained specialists and carries surgical risks [12].…”
Section: Discussionsupporting
confidence: 79%
“…19 In a study done by Kato et al on efficacy of LOD for CC resistant PCOS patients and reported cumulative ovulation rate as 23/32 (71.8%) in women who were treated with LOD followed by CC. 20 Malkawi et al reported, 83.5% ovulation rate in LOD plus CC group and successful ovulation rate of 70.6% and 66.7% with human menopausal gonadotropins (hMG) and pure follicle stimulating hormone (FSH) respectively. 21,22 In present study, inGroup A, out of 12 ovulated women in 1st cycle, 1 (8.3%) got pregnant.…”
Section: Resultsmentioning
confidence: 99%